Nurses' Empathy in Different Wards: A Cross-Sectional Study - Fatemeh Ghaedi; Elaheh Ashouri; Mozhgan Soheili; Mohsen Sahragerd (Wolters Kluwer Medknow Publications, 2020)
Background: Empathy is an important component of the nurse-client relationship and nursing care. The current study aimed to compare nurses' level of empathy with patients in critical care units, psychiatric, and emergency wards. Materials and Methods: The present cross-sectional study was conducted on 112 nurses selected by convenience sampling in three educational hospitals affiliated with Isfahan University of Medical Sciences, Iran from June to September 2017. Data collection tool was a two-part questionnaire consisting of sociodemographic data (such as age, gender, and work experience) and Jefferson Scale of Empathy (JSE) containing 20 items, scored according to Likert scale from totally agree (7 points) to totally disagree (1 point). In total, the maximum score was 140 and the minimum score was 20. Data were analyzed using SPSS version 16 as well as descriptive and analytical statistical tests (multiple regression). Results: The mean (SD) empathy score of nurses working in critical care units, emergency, and psychiatric wards was 87.51 (6.65), 87.59 (4.90), and 90.71 (7.12), respectively. Regarding the regression models, it was observed that only the work experience was a significant predictor for empathy (β = 0.19, p = 0.04). This model predicted 3.50% of variances in the nurses' empathy. Conclusions: Nurses' level of empathy in this study was above average with equal scores in different wards. Therefore, increasing the nurses' level of empathy is essential in interventional studies.